Smart Water Tank Management System Berbasis IoT dan WebSocket untuk Kontrol Dua Pompa Otomatis - Raymondus Trisaptono; Bryant Valencio Marpaung; Willyam Lucas Haposan Sumual; Eka Puji Widiyanto (MDP Student Conference, 2026)
Water management in multi-story buildings requires efficiency to prevent resource wastage. At the Santo Paulus Plaju Catholic Church, manual pump operation frequently leads to tank overflows, water shortages, and potential pump damage due to dry-running. This study designs a centralized automatic control system for filling and booster pumps using an ESP32 microcontroller and Websocket protocol for real-time monitoring. The system integrates an AJ-SR04M ultrasonic sensor for level measurement and a YF-S201 flowmeter for discharge detection. Testing results demonstrate system successfully automates operations based on hysteresis logic (ON <25%, OFF >90%) and flow detection (>4.0 L/m). Furthermore, the Websocket-based interface achieves data update latency under 1 seconds, ensuring a responsive and transparent management solution.